Criminal Law Policy on Carding in Indonesia: Addressing Legal Certainty and Regulatory Fragmentation - Frensh, Wenggedes; Zulyadi, Rizkan; Dhaneswara, Nindya (APPTHI, 2025)
This study examines the adequacy of legal regulations governing credit card misuse (carding) in cyberspace in Indonesia and their implications for legal certainty and law enforcement effectiveness. Using a normative juridical method, it analyzes key statutes, including Law No. 1 of 2024 (EIT Law amendment), Law No. 27 of 2022 on Personal Data Protection, and Law No. 1 of 2023 on the Criminal Code, supported by conceptual and doctrinal approaches. The findings show that, although these regulations provide a general framework for addressing cybercrime, they remain fragmented and do not explicitly regulate carding as a distinct offense. This gap weakens legal certainty and limits effective enforcement. Two main issues are identified: the absence of specific criminal norms on carding and the lack of harmonization across criminal, cyber, and data protection laws. Current legal policy is also predominantly repressive, with limited preventive and victim-oriented measures.